RANCANG BANGUN ALAT PENCAMPURAN CAT AIR 3 WARNA DASAR BERBASIS MIKROKONTROLER - Wijaya, Haji; Sulaiman, Sulaiman; Ariandi, Muhammad; Dasmen, Rahmat Novrianda (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Research and development in the paint industry continue to evolve along with market demands for innovative and high-quality paint products. This study focuses on the development of an automated microcontroller-based paint mixing device to enhance the efficiency and quality of products in the paint industry. The process of mixing basic paint materials, such as pigments, binders, and solvents, is often carried out manually, which is prone to inaccuracy and takes more time. The application of microcontrollers in paint mixing offers a more precise and automated solution, allowing better control over mixing consistency and parameters. Test results show that this device can produce accurate color mixing using the TCS3200 color sensor to detect RGB variations, as well as an ultrasonic sensor to detect the presence of objects during the mixing process. Mixing various primary colors demonstrated consistent results, with mixing times varying depending on the complexity of the mixture.Keywords: Automatic paint mixing, microcontroller, TCS3200 color sensor, ultrasonic sensor, production efficiency, color consistency, paint industry, automation, RGB, and basic material mixingResearch and development in the paint industry continue to evolve along with market demands for innovative and high-quality paint products. This study focuses on the development of an automated microcontroller-based paint mixing device to enhance the efficiency and quality of products in the paint industry. The process of mixing basic paint materials, such as pigments, binders, and solvents, is often carried out manually, which is prone to inaccuracy and takes more time. The application of microcontrollers in paint mixing offers a more precise and automated solution, allowing better control over mixing consistency and parameters. Test results show that this device can produce accurate color mixing using the TCS3200 color sensor to detect RGB variations, as well as an ultrasonic sensor to detect the presence of objects during the mixing process. Mixing various primary colors demonstrated consistent results, with mixing times varying depending on the complexity of the mixture. Keywords: Automatic paint mixing, microcontroller, TCS3200 color sensor, ultrasonic sensor, production efficiency, color consistency, paint industry, automation, RGB, and basic material mixing